Efficacy and safety of electroacupuncture in acute decompensated heart failure: a study protocol for a randomized, patient- and assessor-blinded, sham controlled trial - Jungtae Leem; Seung Min Kathy Lee; Jun Hyeong Park; Suji Lee; Hyemoon Chung; Jung Myung Lee; Weon Kim; Sanghoon Lee; Jong Shin Woo (BMC, 2017)
Abstract Background The purpose of this trial is to evaluate the effectiveness and safety of electroacupuncture in the treatment of acute decompensated heart failure compared with sham electroacupuncture. Methods This protocol is for a randomized, sham controlled, patient- and assessor-blinded, parallel group, single center clinical trial that can overcome the limitations of previous trials examining acupuncture and heart failure. Forty-four acute decompensated heart failure patients admitted to the cardiology ward will be randomly assigned into the electroacupuncture treatment group (n = 22) or the sham electroacupuncture control group (n = 22). Participants will receive electroacupuncture treatment for 5 days of their hospital stay. The primary outcome of this study is the difference in total diuretic dose between the two groups during hospitalization. On the day of discharge, follow-up heart rate variability, routine blood tests, cardiac biomarkers, high-sensitivity C-reactive protein (hs-CRP) level, and N-terminal pro b-type natriuretic peptide (NT-pro BNP) level will be assessed. Four weeks after discharge, hs-CRP, NT-pro BNP, heart failure symptoms, quality of life, and a pattern identification questionnaire will be used for follow-up analysis. Six months after discharge, major cardiac adverse events and cardiac function measured by echocardiography will be assessed. Adverse events will be recorded during every visit. Discussion The result of this clinical trial will offer evidence of the effectiveness and safety of electroacupuncture for acute decompensated heart failure. Trial registration Clinical Research Information Service: KCT0002249 .